PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA DAN IPA YANG TERINTEGRASI DENGAN NILAI BUDAYA LOKAL PADA SMP YPK TOMER - Supriyadi Supriyadi; Andi Saparuddin Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
SMP YPK Tomer is located in Naukenjerai District, where the majority of the population is indigenous Papuans, the Kanum Tribe. Most SMP YPK Tomer students have a way of thinking, and a lifestyle that is still very thick with the cultural principles that develop in their community. The purpose of this training is to provide education and equip math and science teachers at SMP YPK Tomer with the skills to choose and design mathematics and science learning media that are integrated with local cultural values (in this case the Kanum tribe associated with Kampung Tomer). Training and mentoring are designed using ethnomatematics and etnosains which are learning mathematics and science by involving local cultural values. The results of this service are obtained: ruler and protractor media, spatial structure, simple conductivity test material, and air purifier. The response strongly agrees that students are given the learning media for the readability criteria of 87%, the free criteria are used at 73%, and the accessibility criteria is 81%.